Cities in the world. A new perspective on urbanisation. - (:unkn) unknown (My University, 2020)
Cities are not only home to around half of the global population but also major centers of economic activity and innovation. Yet, so far there has been no consensus of what a city really is. Substantial differences in the way cities, metropolitan, urban, and rural areas are defined across countries hinder robust international comparisons and an accurate monitoring of Sustainable Development Goals. The report "Cities in the World" addresses this void and provides new insights on urbanisation by applying for the first time two new definitions of human settlements to the entire globe: the "Degree of Urbanisation" and the "Functional Urban Area". Based on the definitions, the report presents new evidence of recent and future urbanisation trends and sheds light on the evolution of metropolitan areas around the globe. It examines whether and why quality of life differs between cities and other types of settlements. It analyses the relationship between economic development and the metropolitan system in countries around the world. Finally, it presents new evidence on the changing shape of cities and its impact on sustainability. The report demonstrates how globally consistent definitions of cities and metropolitan areas can contribute to more effective policy design.
Keywords: Stadt; Großstadt; Ballungsraum; Metropolregion; Stadtumland; Urbanisierung; Verstädterung; Siedlungsstruktur; Nachhaltige Raumentwicklung; Begriffsbestimmung; Klassifizierung; Degree of urbanisation